The Brain Health Champion study: Health coaching changes behaviors in patients with cognitive impairment - Schwartz, Hope E.M. (Alzheimers Dement (N Y), 2019)
INTRODUCTION: Converging evidence suggests that increasing healthy behaviors may slow or prevent cognitive decline. METHODS: We piloted a six-month, randomized, controlled investigation of 40 patients with mild dementia, mild cognitive impairment, or subjective cognitive decline. The intervention consisted of weekly motivational interviewing phone calls and three visits with a “Brain Health Champion” health coach, who guided participants to achieve personalized goals. Changes in behavior were measured using validated questionnaires. RESULTS: Compared with the standard-of-care control group, Brain Health Champion participants had statistically significant and clinically meaningful increases in physical activity (Cohen's d = 1.37, P < .001), adherence to the Mediterranean diet (Cohen's d = 0.87, P = .016), cognitive/social activity (Cohen's d = 1.09, P = .003), and quality of life (Cohen's d = 1.23, P < .001). The magnitude of behavior change strongly predicted improvement in quality of life. DISCUSSION: Our results demonstrate the feasibility and potential efficacy of a health coaching approach in changing health behaviors in cognitively impaired and at-risk patients.